Caries progression in non-cavitated fissures after infiltrant application: a 3-year follow-up of a randomized controlled clinical trial - Camillo ANAUATE-NETTO; Laurindo BORELLI NETO; Ricardo AMORE; Vinicius DI HIPÓLITO; Paulo Henrique Perlatti D'ALPINO
Abstract Objectives To evaluate the efficacy of a conservative treatment to prevent the progression of caries using an infiltrant on non-cavitated pit and fissures. Material and Methods This controlled clinical trial selected 23 volunteers with clinically and radiographically non-cavitated occlusal caries among patients presenting a "rather low" to "very high" caries risk. Eighty-six teeth were randomly divided into two experimental groups: teeth receiving a commercial pit-and-fissure sealant (Alpha Seal-DFL) and contralateral teeth receiving Icon infiltrant (DMG). Caries progression was monitored by clinical (laser fluorescence caries detection) and radiographic examination at 12-month intervals over a period of 3 years of monitored caries progression. Probing the sealing materials to detect areas of retention was also used to evaluate marginal integrity. Results Statistical analysis showed no difference in caries progression using laser fluorescence caries detection when both materials were compared, regardless of the evaluation times (p>0.05). No significance was observed when the marginal sealant integrity of both materials was compared, regardless of the evaluation time (p<0.05). Marginal integrity significantly reduced after 1 year for both materials (p<0.05), but remained stable after 2 and 3 years of evaluation, compared with 1-year results (p>0.05). SEM analysis exhibited a more homogeneous sealing for the infiltrant than obtained by the sealant. Conclusions The infiltrant was effective to prevent the caries progression in non-cavitated pit-and-fissures after 3 years of clinical evaluation, comparable with the conventional sealant. The infiltrant also presented better results in terms of caries progression at the 3-year evaluation time using the radiographic analysis.